Second Intervention in Obstetric Hemorrhage - Rawal, S; Rana, A (Journal of Institute of Medicine Nepal, 2013)
Introduction: Obstetric hemorrhage is still one of the dreaded complications that contribute to a maximum number of maternal morbidity and mortality till date. The management of obstetric hemorrhage involves early recognition, assessment and resuscitation. Though dealt with appropriate use of oxytocic agents, it may seldom require surgical techniques, including uterine tamponade, major vessel ligation, compression sutures, and even hysterectomy. Method: Prospective study of 20 cases of laparotomy for obstetrical hemorrhage carried out at Tribhuvan University Teaching Hospital, Kathmandu, Nepal, between Jan 2003 to Nov 2011. Results: Out of 20 cases, massive hemoperitoneum (more than a liter) was noted in 9 and associated risk factors in 10. Source of bleeding in 20 cases were from extensive hematoma (retroperitoneal and broad ligament) in 5, including a rectus sheath hematoma and with colporrhexis, oozing inverted T incision repaired in a single layer (1), placental bed (3) and 1 was from vessels in LUS. There was bleeding from uterine angle (4) and incision (1). Bleeding from tear at various sites were 3, from uterovesicle fold of peritoneum 1 and from the ruptured uterus following vacuum delivery in a case of VBAC (1). Uterine packing was done in 1, B-Lynch in 3 and 1 failed needing the uterine packing; uterine artery ligation in 2 including ovarian vessel ligation in 1, repair of ruptured uterus in 1 and subtotal hysterectomy in 5 cases. There were 3 mortalities due to DIC, pulmonary edema and ARF and rest were discharged in good health. Conclusion: Choosing of the right technique, complete hemostasis and meticulous closure of all surgical incisions will prevent the need for laparotomy following LSCS. Vigilant monitoring of all the post operative patients will lead to early diagnosis of intraperitoneal / pervaginal bleeding and its management, thus preventing morbidity and mortality owing to late diagnosis. DOI: http://dx.doi.org/10.3126/joim.v34i1.9118 Journal of Institute of Medicine, April, 2012; 34:1 18-24